1962
DOI: 10.1038/icb.1962.42
|View full text |Cite
|
Sign up to set email alerts
|

The Immunological Role of Different Lymphoid Organs in the Chicken

Abstract: SUMMARY The development of lymphoid tissue in the bursa of Fabricius in the chicken has been prevented by the injection in ovo of testosterone propionate. A small proportion of the hatched chickens were also shown to have a complete atrophy of the thymic cortex. The immunological responses of these hormonally‐treated chickens have been studied using several types of antigenic challenge. In birds deprived of all bursal lymphoid tissue, but still possessing a normal thymus, no circulating antibody was detected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

1966
1966
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(40 citation statements)
references
References 0 publications
1
38
1
Order By: Relevance
“…It may be conclud ed, therefore, that the germinal center formation is a phenomenon which is, at least partially, influenced by the development of the thymic and/or thymus dependent lymphoid tissue. This conclusion coincides in part with those that were drawn by Warner et al (1962) and Jankovic and Mitrovic (1967). White et al (1967White et al ( , 1970 observed that new germinal centers arose within masses of the periarterial lymphoid tissue.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…It may be conclud ed, therefore, that the germinal center formation is a phenomenon which is, at least partially, influenced by the development of the thymic and/or thymus dependent lymphoid tissue. This conclusion coincides in part with those that were drawn by Warner et al (1962) and Jankovic and Mitrovic (1967). White et al (1967White et al ( , 1970 observed that new germinal centers arose within masses of the periarterial lymphoid tissue.…”
Section: Discussionsupporting
confidence: 77%
“…A considerable suppression of the development of thymus-dependent lymphoid tissue in the chicken has been produced by surgical thymectomy at hatching (Warner et al 1962;Jankovic and Isakovic 1964) or surgical thymectomy combined with whole body X-irradiation in the newly hatched period (Cooper et al 1965). …”
Section: Discussionmentioning
confidence: 99%
“…Antisera absorbed in this manner have binding properties comparable to those prepared by the more rigorous methods employed in this investigation. DISCUSSION A congeries of evidence from studies in the chicken (19,20), mouse (21-23), rat (1)(2)(3)(4)24), and other mammalian species including man (25) has established the existence of at least two developmentally and functionally distinct populations of lymphocytes. T lymphocytes are produced under the influence of the thymus, whereas B lymphocytes arise from stem cells in the bone marrow and are formed in both normal and thymectomized subjects.…”
Section: Makeup Of Lymphocyte Populations In Txbmmentioning
confidence: 99%
“…Noting that in ovo treatment with testosterone sometimes impaired thymus development and the ability to reject allografts, Alexander Szenberg and Noel Warner 28 suggested in 1962 that the thymus and the bursa have different functions. Their results suggested a model in which the thymus controls allograft rejection, the bursa controls antibody production and delayedtype hypersensitivity, and the bone marrow is responsible for graft-versus-host reactivity 29 . Raymond Peterson and co-workers 30 found that bursectomy prevented the development of virus-induced lymphomas, whereas thymectomy had no effect.…”
Section: Cellular Versus Humoral Immunitymentioning
confidence: 99%